KAPASITAS VITAL PARU-PARU, PANJANG TUNGKAI, KEKUATAN OTOT TUNGKAI DAN PRESTASI LARI 800 METER - Basuki, Sunarno (Vidya Karya, 2016)
Abstract. This study intends to study the relationship between the vital lung capacity, leg length, and leg muscle strength to describe the 800m run achievement of SMP 2 Banjarbaru South Kalimantan students.  The purpose of this study was to determine: 1) The relationship between the vital capacity of the lungs and the run achievement of 800m. 2) The relationship between the leg length and the run achievements of 800m. 3) The relationship between leg muscle strength and the run achievements of 800m. 4) The relationship between leg muscle strength, leg length,  together with vital lung capacity and the run achievement of 800m. The method used in this study is correlational while the data collected by using tests and measurements. The population in this study were 8th grade students of SMP Negeri 2 Banjarbaru consisting of 315 students. Of 32 students were selected being the samples determined by purposive. Data analysis was conducted by using product moment correlation technique. The study showed that: 1) There is no relationship between the vital capacity of the lungs and the run achievement of 800m. 2) There is no relationship between the length of the leg and the run achievements of 800m. 3) There is a relationship between leg muscle strength and the run achievements of 800m. 4) There is a relationship between the vital lung capacity, leg length together with leg muscle strength and the run achievements of 800m. Keywords:  relationship, vital lung capacity, the lengths of the leg,  leg muscle strength, the run achievements of 800m. Abstrak. Penelitian ini bermaksud mempelajari hubungan antara faktor kapasitas vital paru-paru, panjang tungkai, dan kekuatan otot tungkai untuk menggambarkan prestasi lari 800 meter siswa SMP Negeri 2 Banjarbaru Kalimantan Selatan. Tujuan penelitian adalah untuk mengetahui: 1) hubungan antara kapasitas vital paru-paru dengan prestasi lari 800 meter, 2) hubungan antara panjang tungkai dengan prestasi lari 800 meter, 3)   hubungan antara kekuatan otot tungkai dengan prestasi lari 800 meter, 4) hubungan antara kekuatan otot tungkai, panjang tungkai dan kapasitas vital paru-paru dengan prestasi lari 800 meter. Metode yang digunakan dalam penelitian ini adalah metode korelasional dengan teknik pengambilan data melalui tes dan pengukuran. Populasi dalam penelitian ini adalah peserta didik SMP Negeri 2 Banjarbaru kelas 8 berjumlah 315 orang dengan sampel penelitian berjumlah sampel 32 orang yang ditetapkan secara purposive. Analisis data dilakukan dengan menggunakan teknik  korelasi produk moment. Hasil penelitian menunjukkan bahwa: 1) Tidak ada hubungan antara kapasitas vital paru-paru  dengan prestasi lari 800 meter. 2) Tidak ada hubungan antara panjang tungkai  dengan prestasi lari 800 meter. 3) Ada hubungan antara kekuatan otot tungkai  dengan prestasi lari 800 meter. 4) Ada hubungan antara kapasitas vital paru-paru, panjang tungkai dan kekuatan otot tungkai  dengan prestasi lari 800 meter. Kata kunci:  Hubungan, kapasitas vital paru, panjang tungkai, kekuatan otot tungkai, prestasi lari 800 meter